2005
DOI: 10.1017/s0033291705005428
|View full text |Cite
|
Sign up to set email alerts
|

Neuregulin 1 (NRG1) and schizophrenia: analysis of a US family sample and the evidence in the balance

Abstract: Our failure to find an association between NRG1 and schizophrenia might reflect different linkage disequilibrium (LD) patterns found in different populations, disease allelic heterogeneity, clinical heterogeneity of schizophrenia, or inadequate statistical power deriving from moderate sample size. NRG1, if a true gene for schizophrenia, accounts for a small fraction of the disease in most populations. The confirmation of NRG1 as a schizophrenia susceptibility gene will require studies with a comprehensive set … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 0 publications
1
26
0
Order By: Relevance
“…53 On 8p21-p12 lies the second of the two most strongly implicated susceptibility genes, neuregulin1 (NRG1), 45 although other reports could not replicate this finding. 54 NRG1 is associated with synaptic remodeling, neuronal migration and brain development and appears to influence glutamatergic function through regulation of NMDA receptors. 55,56 Further, NRG1 has been studied to have a key role in neurodevelopmental process in central nervous system (CNS) that includes oligodendrocyte development.…”
Section: Chromosomes 6 Andmentioning
confidence: 99%
“…53 On 8p21-p12 lies the second of the two most strongly implicated susceptibility genes, neuregulin1 (NRG1), 45 although other reports could not replicate this finding. 54 NRG1 is associated with synaptic remodeling, neuronal migration and brain development and appears to influence glutamatergic function through regulation of NMDA receptors. 55,56 Further, NRG1 has been studied to have a key role in neurodevelopmental process in central nervous system (CNS) that includes oligodendrocyte development.…”
Section: Chromosomes 6 Andmentioning
confidence: 99%
“…As estimated by TDT-PC (transmission disequilibrium testpower calculator) software [40] , our sample has about 87% power to detect a locus with a relative risk (RR) of 2 at a significance level of 5%; but power drops to 44% for an RR of 1.4 [41] . [8] .…”
Section: Subjects and Phenotypingmentioning
confidence: 99%
“…Chromosome 8p has been suggested repeatedly as a linkage region for both SZ and BPD; however, the underlying genes responsible for the linkage signal remain elusive. NRG1 was identified as one candidate gene from this region and was associated with SZ (Stefansson et al, 2002(Stefansson et al, , 2003Williams et al, 2003;Yang et al, 2003;Corvin et al, 2004;Li et al, 2004;Tang et al, 2004;Petryshen et al, 2005) and BPD (Green et al, 2005) in some studies but could not be confirmed by others (Bakker et al, 2004;Hong et al, 2004;Iwata et al, 2004;Thiselton et al, 2004;Duan et al, 2005;Liu et al, 2005). This inconsistency might be due to several factors including clinical heterogeneity, population stratification, different haplotype structure between populations, and limited statistical power.…”
Section: Vmat1 and Bipolar Disordermentioning
confidence: 99%
“…Recent linkage studies have suggested that a susceptibility locus for BPD exists on chromosome 8p21-22 (Cichon et al, 2001;Ophoff et al, 2002;Park et al, 2004;Cheng et al, 2006). Interestingly, numerous linkage studies in schizophrenia (SZ) report a susceptibility locus on 8p21 (Pulver et al, 1995(Pulver et al, , 2000Kendler et al, 1996;Straub et al, 1996;Blouin et al, 1998;Brzustowicz et al, 1999;Gurling et al, 2001;Stefansson et al, 2002;Lewis et al, 2003;Suarez et al, 2006) and a candidate gene from this region, neuregulin 1 (NRG1), was associated with SZ (Stefansson et al, 2002(Stefansson et al, , 2003Williams et al, 2003;Yang et al, 2003;Corvin et al, 2004;Li et al, 2004;Tang et al, 2004;Petryshen et al, 2005); however, NRG1 is located about 10-15 cM away from the major linkage peaks and others could not confirm an association between the NRG1 gene and SZ (Bakker et al, 2004;Hong et al, 2004;Iwata et al, 2004;Thiselton et al, 2004;Duan et al, 2005;Liu et al, 2005). The report of multiple linkage studies in BPD and SZ supports the hypothesis of a shared susceptibility locus for BPD and SZ on 8p (Berrettini, 2003(Berrettini, , 2004.…”
Section: Introductionmentioning
confidence: 99%